The Future of E-voting Implementation in Indonesian General Election Process: Constitutionality, Benefits and Challenges - Fahri Bachmid; Hardianto Djanggih (Fakultas Hukum Universitas Muhammadiyah Magelang, 2022)
The emergence of the COVID-19 pandemic has hampered the conduct of general elections in a number of countries. In the previous simultaneous regional elections in 2020, there was an increase in positive cases of COVID-19, which resulted in fatalities. This study seeks to examine the possibility of electronic voting (E-Voting) as an alternative policy to ensure safe elections during a pandemic, by examining the aspects of constitutionality, advantages, and challenges of its implementation.. This research employs a normative research methodology with a conceptual, constitutional, and comparative approach. The result shows that, from a constitutional standpoint, the protocol for implementing E-Voting is consistent with the principles of direct, general, free, confidential, honest, and fair elections mandated in the Republic of Indonesia's 1945 Constitution, and thus can be used as an alternative election policy in the future. E-voting also offer potential benefits for the democratic, efficient, and secure electoral system that can be used in the current pandemic situation. However, there are a number of obstacles to its implementation in Indonesia due to systemic flaws in e-voting, such as its security and validity, as well as the condition of voters and insufficient infrastructure in the Indonesian context.